Hodnocení finanční situace podniku a jeho zabezpečení informačním systémem - Štarha, Jan (Vysoké učení technické v Brně. Fakulta podnikatelská, 2011)
Předmětem bakalářské práce je zhodnocení finanční situace společnosti FEI Czech Republic s.r.o. v letech 2006 až 2009 a analýza informačních systémů které finanční oddělení primárně používá. Na základě analýz jsou potom vytvořeny návrhy na zlepšení finanční situace podniku především pomocí změn a inovací informačních systémů společnosti.

The subject of this Bachelor's thesis is an evaluation of the financial situation relating to the company FEI Czech Republic s.r.o. from years 2006 to 2009 and the analysis of an information systems which are primarly used by this company. Based on these analysis there are ideas created to improve the financial situation of the company mainly by changes and inovations of an information systems.
Appraisal of Company's Financial Situation and its Information System Support
Keywords: Finanční analýza; horizontální analýza; vertikální analýza; rozdílové ukazatele; poměrové ukazatele; rozvaha; výkaz zisku a ztrát; výkaz cashflow; Altmanův index; indexy IN; informační systém; ERP systémy.; Financial analysis; horizontal analysis; vertical analysis; differential indicators; ratio indicators; balance; profit and loss statement; cash flow statement; Altman index; IN index; information system; ERP systems.